Eksplorasi Paragraf dan Ragam Teks: Analisis Struktur dan Fungsinya - Bunga Machfira S; Balqis Nila F; Adinda Siti A; Nadia Nur Afrida; Ismail Mubarok (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
A paragraph is the smallest unit in written discourse which has an important role in building text cohesion and coherence. However, a lack of understandiag of the structure and function of paragraphs often becomes an obstacle in writing, especially in the context of learning Indonesian at the high school level. This research aims to analyze the structure and function of paragraphs in various types of text, such as narrative, descriptive and expository, and identify patterns that support communication effectiveness. This research uses a qualitative method with a content analysis approach. Data were obtained from five Indonesian high school level textbooks chosen randomly. The analysis focuses on paragraph structure (subject, predicate, object) and characteristics of text types. The research instrument includes guidelines for paragraph structure analysis, classification of text types, and criteria for effective paragraphs. The research results show that each type of text has a unique paragraph structure and function pattern, in accordance with its communication objectives. Narrative paragraphs support the storyline, descriptive create images, and expository convey factual information logically. In conclusion, understanding the structure and function of paragraphs can improve students' writing skills. This research recommends strengthening learning strategies that focus on analyzing paragraph structure and text variety to improve students' writing skills effectively.